Intertwined: What makes food and wine pairings appropriate?. (October 2020) - Kustos, Marcell; Heymann, Hildegarde; Jeffery, David W.; Goodman, Steve; Bastian, Susan E.P.
Graphical abstract: Highlights: Liking and sensory complexity of wines increased in appropriate pairings. Consumers preferred pairings with slight wine dominance and more complexity. In appropriate pairings consumers expected to pay a higher price for the wine. Flavour intensities of food and wine increased in appropriate pairings. Appropriate consumer segmentation may better account for the variability of results. Abstract: This study sought to identify sensory attributes of appropriate food and wine pairings and relate them to balance, consumer liking, sensory complexity, and expected price. A descriptive analysis panel (n = 8) evaluated four Australian Shiraz wines along with four complex food samples, yielding 16 wine and food combinations. Based on the sensory profiles, distinct food and wine pairings (n = 6) were selected for consumer preference tests, comprising a real life, pseudo-three course meal with two wines. According to American consumers (n = 108), in the most appropriate pairings, flavour intensities increased and wine taste attributes changed in relation to individual components. Appropriate pairings positively correlated with liking, sensory complexity, and expected price to pay, and negatively with balance as a slight wine dominance was preferred. Pairings had an increase in liking and sensory complexity over the individual wine but not the food component. To account for individual variability, consumers were segmented by their liking of the pairing. Key drivers of successful pairings across consumer clusters were similar to the average consumer results, however, the preferred pairings differed by cluster. The findings suggest, the quality of food and wine pairings might be better measured with a combination of direct (dominance/balance, appropriateness of pairing) and indirect methods (sensory complexity, liking), instead of a single scale, and consumer segmentation may better account for the variability of results. The outcome of this study enhanced the understanding of the relationship between consumer behaviour and food and wine pairings.